The Influence of Gross Domestic Product and SBI on Tax Revenue in Indonesia - Prasetyo, Rio Arif (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the influence of net domestic product and SBI on tax revenue in Indonesia with the independent variables net domestic product and SBI as well as the dependent variable tax revenue. The data is time series data between 1911 – 2023 using the Ordinary Least Square (OLS) method and the formula model used is multiple linear regression. The research results show that clean domestic product has a positive and significant effect on tax revenues in Indonesia at the 99% level. Meanwhile, SBI has a negative and significant influence on tax revenues in Indonesia at a level of 90%.